Corrosion and Wear Properties of Cold Rolled 0.087% Gd Lean Duplex Stainless Steels for Neutron Absorbing Material - Yong Choi; Youl Baik; Byung-Moon Moon; Dong-Seong Sohn (Nuclear Engineering and Technology, 2016)
Lean duplex stainless steels with 0.087 wt.% gadolinium (Gd) were inert arc-melted and cast in molds of size 10 mm × 10 mm × 20 mm. The micro-hardnesses of the rolling direction (RD), transverse direction (TD) and short transverse (ST) direction were 258.5 HV, 292.3 HV, and 314.7 HV, respectively. A 33% cold rolled specimen had the crystallographic texture that (100) pole was mainly concentrated to the normal direction (ND) and (110) pole was concentrated in the center of ND and RD. The corrosion potential and corrosion rate in artificial seawater and 0.1M H2SO4 solution were in the range of 105.6–221.6 mVSHE, 0.59–1.06 mA/cm2, and 4.75–8.25 mVSHE, 0.69–1.68 mA/cm2, respectively. The friction coefficient and wear loss of the 0.087 w/o Gd-lean duplex stainless steels in artificial seawater were about 67% and 65% lower than in air, whereas the wear efficiency was 22% higher. The corrosion and wear behaviors of the 0.087 w/o Gd-lean duplex stainless steels significantly depended on the Gd phases.